Intussusception after injury to the small intestine during emergent cesarean delivery of a premature triplet pregnancy: A case report - Allen Star; Valeria Ripa; Fariha Sheikh; Wei Wei Zhang (Elsevier, 2022)
Intussusception is a rare cause of intestinal obstruction in the postoperative setting. This report describes a rare case of intussusception in the early postoperative period following an emergent cesarean delivery of a premature triplet pregnancy, where the small intestine was fully transected. The intestine was repaired with a stapled primary side-to-side functional end-to-end anastomosis. Five days after being discharged, the patient was readmitted due to a small bowel obstruction due to intussusception. The anastomotic site was acting as the lead point, and it required resection. Bowel continuity was reestablished with a hand-sewn anastomosis in end-to-end fashion. The patient had an uneventful recovery and was discharged home. All three neonates were eventually discharged home and the patient was able to start breast feeding. This is believed to be the first case in the obstetric literature where intussusception occurred after intestinal repair of transected bowel during an obstetric emergency.